Reduced cardiovagal baroreflex sensitivity is associated with postural orthostatic tachycardia syndrome (POTS) and pain chronification in patients with headache - Mueller, Bridget R.; Ray, Carly; Benitez, Alyha; Robinson-Papp, Jessica (Frontiers in Human Neuroscience, 2023)
Background: Non-cephalgic symptoms including orthostatic intolerance, fatigue, and cognitive impairment, are common in patients with chronic headache disorders and may result from alterations in the autonomic nervous system. However, little is known about the function of autonomic reflexes, which regulate cardiovascular homeostasis and cerebral perfusion in patients with headache. Methods: Autonomic function testing data from patients with headache collected between January 2018 and April 2022 was retrospectively analyzed. Through review of EMR we determined headache pain chronicity and patient self-report of orthostatic intolerance, fatigue, and cognitive impairment. Composite Autonomic Severity Score (CASS), CASS subscale scores, and cardiovagal and adrenergic baroreflex sensitivities were used to quantify autonomic reflex dysfunction. Descriptive analyses (Mann-Whitney-U or χ2, as appropriate) determined associations between autonomic reflex dysfunction and POTS as well as chronic headache. Binomial logistic regression adjusted for age and sex. Spearman's rank correlation determined the association between the total CASS score and the number of painless symptoms reported by each participant. Results: We identified 34 patients meeting inclusion criteria, of whom there were 16 (47.0%) with orthostatic intolerance, 17 (50.0%) with fatigue, 11 (32.4%) with cognitive complaints, and 11 (32.4%) with Postural Orthostatic Tachycardia Syndrome (POTS). The majority of participants had migraine (n=24, 70.6%), were female (n=23, 67.6%) and had a chronic (>15 headache days in a month) headache disorder (n=26, 76.5%). Reduced cardiovagal baroreflex sensitivity (BRS-V) independently predicted chronic headache (aOR: 18.59 [1.16, 297.05], p=0.039) and POTS (aOR: 5.78 [1.0, 32.5], p = 0.047). The total CASS was correlated with the total number of non-painful features in the expected direction (r = 0.46, p = 0.007). Conclusions: Abnormal autonomic reflexes may play an important role in pain chronification and the development of POTS in patients with headache.